Estetica e teleologia - Maurizio Ferraris (Rivista di Estetica, 2017)
Taking aesthetics as epistemology (in agreement with Emilio Garroni’s perspective) means taking aesthetics as teleology, namely as the need for knowledge to attribute a purpose to what is known. Art has the ability to anticipate these purposes, letting them emerge even if there is insufficient evidence.